South American snake venom proteins antigenically-related to Bothrops asper myotoxins. - Lomonte, Bruno (1990)
the presence of proteins antigenically related to Bothrops asper myotoxins in various snake venoms, mainly from South America, was investigated by using poluclonal and monoclonal antibodies. 2. Myotoxin-like components were detected in the bothrops venoms from South america, and in the venoms of Crotalus atrox (North america), Trimerusurus flavoviridis (Japan), and Micrurus alleni (Costa Rica). 3. Cross-reactive components detected in several Bothrops venoms show a common subunit of 15-16 LDa by sodium dodcyl sulphate-polyacrylamide gel electrophoresis, although significant charge variations are evident by immunoelectrophoresis. 4. It is concluded that proteins antigenically related to B. asper nyotoxins are relatively common in the genus Bothrops and, in the light of findings discussed, are likely to posses myotoxic activity.